Freedom from the known - Krishnamurti, J.; Lutyens, Mary (ed.) (London Rider, 2010)
Krishnamurti shows how people can free themselves radically and immediately from the tyranny of the expected, no matter what their age--opening the door to transforming society and their relationships.